Pendidikan Profetik dan Perannya dalam Menangkal Dampak Negatif Teknologi di Mlangi Yogyakarta - Habiba, Sulhatul; Sholikhah, Khotimatus (Al-Riwayah : Jurnal Kependidikan, 2018)
This research describes the prophetic education in Mlangi Nogotirto Gamping Sleman Yogyakarta, and examines the role it plays in counteracting the negative effects of technology. Problem formulation in this research: what is the meaning of prophetic education? and how does prophetic education stem the negative effects of technology? The results show that prophetic education plays a major role in minimizing the negative effects of technology. The strengthening of spirituality as played by 16 pesantren and active involvement of citizens and santri in society can counter the negative influence from outside Mlangi.